Combining Whispering‐Gallery Mode Optical Biosensors with Microfluidics for Real‐Time Detection of Protein Secretion from Living Cells in Complex Media. Issue 22 (2nd May 2018) - Chen, Ying‐Jen; Schoeler, Ulrike; Huang, Chung‐Hsuan (Benjamin); Vollmer, Frank
Abstract: The noninvasive monitoring of protein secretion of cells responding to drug treatment is an effective and essential tool in latest drug development and for cytotoxicity assays. In this work, a surface functionalization method is demonstrated for specific detection of protein released from cells and a platform that integrates highly sensitive optical devices, called whispering‐gallery mode biosensors, with precise microfluidics control to achieve label‐free and real‐time detection. Cell biomarker release is measured in real time and with nanomolar sensitivity. The surface functionalization method allows for antibodies to be immobilized on the surface for specific detection, while the microfluidics system enables detection in a continuous flow with a negligible compromise between sensitivity and flow control over stabilization and mixing. Cytochrome c detection is used to illustrate the merits of the system. Jurkat cells are treated with the toxin staurosporine to trigger cell apoptosis and cytochrome c released into the cell culture medium is monitored via the newly invented optical microfluidic platform. Abstract : The integration of a resonance‐based optical sensor called a whispering gallery mode biosensor with a microfluidic system provides an effective tool for monitoring protein secretion of cells responding to drug treatment. The sensor surface is functionalized with anticytochrome c antibodies to specifically detect cytochrome c secretion from cells into the surrounding media in real‐time after drug treatment.